Analisa Pengendalian Kualitas Kadar Air pada Proses Pakan Ikan Floating dengan Metode Peta Kendali Variabel X Dan R Di PT Sinta Prima Feedmill - Nurrokhman, Agus; Pitono, Wuguh (Universitas Pamulang, 2025)
This research was conducted with the aim of knowing the quality of floating feed at PT. Sprott Prima Feedmill. The method used is the Average Control Chart (X) and the Range Control Map (R). The samples taken were 20 times and 5 observations were taken for each sample. From the Average Control Map, the results show that the quality of the floating feed is still within reasonable limits or the quality is still guaranteed by looking at the points that are not outside the upper control limit or UCL, which is 8.48 or the lower control limit or LCL, which is 5.95. From the Range Control Map, the results show that the quality of the floating feed is also within reasonable limits or the quality is still guaranteed by looking at the points that are not outside the upper control limit or UCL, namely 3.09 or the lower control limit or LCL 0. So it can be concluded that the feed quality floating at PT. Sinta Prima Feedmill guaranteed quality.